BOSHLANG'ICH SINFLARDA INGLIZ TILINI O'QITISHNING SAMARALI USULLARI - Akbarova Durdona Mahmudjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
This article provides information on productive, modern and innovative methods of teaching English, in order to get learners more interested in primary classes.